PDCT-06. PHASE 1 STUDY OF ONC201 IN PEDIATRIC PATIENTS WITH H3 K27M-MUTANT HIGH GRADE GLIOMA OR NEWLY DIAGNOSED DIPG. (5th November 2018) - Gardner, Sharon; Suarez, Fernando; Stafford, James M; S. Tarapore, Rohinton; Merdinger, Krystal; Oster, Wolfgang; Allen, Joshua; S. Chi, Andrew; Fuller-Becker, Hope; Yaffe, Anna; C. Allen, Jeffrey
Abstract: The imipridone ONC201 is the first selective antagonist of DRD2 for clinical oncology. Several Phase 1, Phase 1/2 and Phase 2 studies in patients with advanced cancers have established the single agent recommended Phase 2 dose (RP2D) of 625mg ONC201 administered orally once a week in adults. ONC201 induces p53-independent apoptosis in newly diagnosed and recurrent high-grade glioma in vitro, ex vivo and in vivo. Furthermore, radiographic regressions in adult recurrent H3 K27M-mutant glioblastoma patients in response to single agent ONC201 have been reported. Based on this adult experience and complementary preclinical results demonstrating the increased susceptibility of H3 K27M-mutant gliomas to ONC201, we initiated the first Phase 1 pediatric clinical trial of ONC201 January 30, 2018. This trial will determine the safety and RP2D of ONC201 in pediatric post-radiation H3 K27M-mutant glioma patients as a single agent and in newly diagnosed diffuse intrinsic pontine glioma (DIPG) patients in combination with radiation (NCT03416530). Patients without known H3 K27M-mutation status by a CLIA-lab can enroll with commitment to post-term biopsy. This is a multicenter, open-label, 2 arm, dose-escalation and dose-expansion study. Ten children with H3 K27M-mutant gliomas ages 5–18 years have been treated post-radiation: 3 at dose level 1; 3 at dose level 2; 4 as part of the dose expansion cohort on dose level 2. Patients have received 2–12 doses (median= 5). The ONC201 has been tolerated very well. Grade III/IV events include: decreased neutrophil count grade III (n=1) spontaneously resolved without dose modification and elevated AST grade III (n=1) returned to grade II after holding 1 dose. Additional safety data as well as pharmacokinetics, pharmacodynamics, and progression-free survival results from this trial will be reported.